Supervisory control and data acquisition meets public policy - a Glenn-Colusa Irrigation District case study - Kennedy, Pat, author; Bettner, Thaddeus, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2012)
Looking into the future, water agency managers, consultants, board members and other decision makers will need to assess and consider using today's available technology to make more informed decisions to balance competing needs for water, to demonstrate improved water management, and to implement and manage water conservation programs. The initial investment and "growing pains" of using technology to install or update a system can streamline operations and serve multiple functions to improve efficiency and data acquisition. With this foundation, Glenn-Colusa Irrigation District (GCID) elected to proceed with installing and utilizing a Supervisory Control and Data Acquisition (SCADA) system to improve operations and assist in addressing the myriad challenges associated with operating a large irrigation district in California. Internal to GCID, the SCADA system is part of a long-term strategic plan to enable improvements to control the distribution and delivery of irrigation water through GCID's extensive canal network. One of the most important components of GCID's SCADA system is the communication system, which is a high-speed endlessly expandable communication network capable of adding an unlimited amount of SCADA sites. External to GCID, California's policy makers continue to enact new legislation requiring water agencies to prove that they are accurately measuring water, to demonstrate that water is being efficiently managed and beneficially used, and to establish linkages between surface water and groundwater. GCID is in the process of expanding its SCADA system to meet these new public objectives.
Irrigated agriculture responds to water use challenges
SCADA meets public policy
Presented at Irrigated agriculture responds to water use challenges - strategies for success: USCID water management conference held on April 3-6, 2012 in Austin, Texas.